Femina sacra: Gendered memory and political violence - LENTIN, RONIT (Elsevier, 2006)
This article explores a specific form of state sanctioned violence enacted towards survivors of Transnistria, Ukraine, using testimonies of women survivors of Transnistria. The article theorises the woman survivor of genocide as femina sacra ? the equivalent of Agamben's [Agamben, Giorgio (1995) Homo Sacer: Sovereign Power and Bare Life. Stanford, Ca: Stanford University Press.] homo sacer, she who can be killed without charge of homicide but who cannot be sacrificed, and who is always at the mercy of sovereign power. The article then examines the politics of memory in relation to political violence and the concept of postmemory, as developed by Marianne Hirsch [Hirsch, Marianne (1997) Family Frames: Photography, Narrative and Postmemory. Cambridge: Harvard University Press.], denoting a `vicarious past? or `received history?, and the link between feminism and `cultural memory?. It concludes by teasing out a series of interrelated questions about the role gender plays in the interaction of genocide, gender and memory.
PUBLISHED
Keywords: Sociology